Analisis Kenaikan Harga Tiket Pesawat: Studi Kasus Arus Balik Lebaran di Sumatera Barat - Zulman, Herry; Kustati, Martin; Amelia, Rezki (LANCAH: Jurnal Inovasi dan Tren, 2024)
This research is based on the author's observations regarding the increase in airfare prices for Eid homecoming at Minangkabau International Airport. High ticket prices has been ongoing since the era of Tabing Airport, which the author attributes to the strong sense of familial bonds among the Minangkabau people. While some airline passengers know this problematic, the author was intrigued to investigate it. The study focuses on the Padang-Jakarta route, a popular route throughout the year, with the main question being the causes of the high ticket prices on this route. The methodology used is library research. Data analysis relies on regulations from the Ministry of Transportation and examines airline behavior during peak seasons. Data were obtained through library research, direct field observations, and interviews. The research concluded that airlines did not raise fares beyond the regulatory upper limit. Instead, the increase in ticket prices is due to market strategies, service classification modifications, transit ticket prices, and the Online Travel Agent (OTA) system that uses automatic ticket tracking. The main reasons people continue to choose air travel for this preferred route are time efficiency, comfort, and prestige. The author suggests anticipating high ticket prices for Eid homecoming by booking tickets well in advance, looking for promotional prices, utilizing credit card facilities, or using ground transportation to Sultan Syarif Kasim II Airport in Pekanbaru and then traveling to Jakarta.